Psychopathy and Pride: Testing Lykken’s Hypothesis Regarding the Implications of Fearlessness for Prosocial and Antisocial Behavior - Costello, Thomas H.; Unterberger, Ansley; Watts, Ashley L.; Lilienfeld, Scott O. (Frontiers in Psychology, 2018)
Despite widespread assumptions that psychopathy is associated with serious and repeated law-breaking, individuals with psychopathic personality traits do not invariably become chronic criminal offenders. As a partial explanation for this finding, Lykken (1995) ventured that a fearless temperament underlies both psychopathic traits and heroic behavior, and that heroic individuals' early exposure to effective socializing forces such as warm parenting or healthy self-esteem often fosters a characteristic adaption that tends to beget “successful” behaviors, thereby differentiating heroes from convicts. In this study, we investigate relations between psychopathy, principally its Fearless dominance dimension, pride, and prosocial and antisocial behavior in a community sample (N = 339). Fearless dominance and Self-centered Impulsivity components of psychopathy yielded differential relations with authentic and hubristic pride (Tracy & Robins, 2004), such that Fearless dominance was significantly positively correlated with both facets of pride while Self-centered Impulsivity was significantly negatively correlated with authentic pride and significantly positively correlated with hubristic pride. Further, authentic pride moderated (potentiated) the relation between Fearless dominance and transformational leadership, one of the two outcome measures for prosocial behavior employed in our investigation. Authentic pride did not moderate the relations between Fearless dominance and either our other measure of prosocial behavior (heroism) or antisocial behavior, nor did positive parenting moderate the relations between psychopathy components and social behavior. Unexpectedly, hubristic pride significantly moderated the relation between impulsive-antisocial features and antisocial behavior in a protective manner.